The king's whore - Corti, Axel; Raphael, Frederick; Vigne, Daniel; Vidmark Entertainment ([United States : Vidmark Entertainment, 1993)
Arriving at the lavish, 17th century court of the King of Piedmont, beautiful young Jeanne de Luyes suddenly finds herself the object of the king's relentless attentions. Finally, when her husband abandons her to the king, she gives him her body--but she swears she'll never give him her love
Title from title screen
DVD format
With optional English, Chinese or Malay subtitles
Keywords: Feature films